Mechanisms involved in the anti-inflammatory properties of native and genetically engineered lactic acid bacteria - Leblanc, Jean Guy Joseph (2013)
Lactic acid bacteria (LAB) represent a heterogeneous group of microorganisms that have been shown to possess therapeutic properties since they are able to prevent the development of some diseases, as shown mostly on animal models for cancer, infections and gastrointestinal disorders such as intestinal inflammation. LAB have been shown to regulate mucosal immune responses by modulating the production and liberation of regulatory agents such as cytokines by the host. Some of these cytokines, such as the anti-inflammatory interleukin-10 (IL-10), modulate the inflammatory immune response, thus immunomodulation is a mechanism by which LAB can prevent certain inflammatory bowel diseases (IBD). Since oxidative stress participates to the inflammatory processes and to the appearance of damages in pathologies of the gastrointestinal tract of humans such as IBD, LAB could also prevent inflammation by eliminating reactive oxygen species (ROS) through the activity of antioxidant enzymes.In order to obtain novel strains or enhance beneficial effects of LAB, genetic engineering has been used to produce either antioxidant enzymes (such as catalases and superoxide dismutases) or anti-inflammatory cytokines (such as IL-10) producing LAB. These novel strains have successfully been used to prevent inflammatory bowel diseases in animal models and could be evaluated in human clinical trials. Here, we present an overview of the current knowledge of the mechanisms by which LAB can be used to prevent undesired intestinal inflammatory responses and could be used as a therapeutic tool for IBD.